Awareness and knowledge of cardiovascular disease and their associations with the lifestyles of 8-16-year-old girls: a perspective from Saudi Arabia - Maha A. Al-Mohaissen; Sarah Alohali; Ameera Alhariqi; Ahad Alotaibi; Haifa Almedbal; Rabah AlMehisen; Badriah Almasri; Terry Lee (BMC, 2024)
Abstract Background There has been an increased focus on children as a target for primordial prevention of cardiovascular disease (CVD). In particular, girls should receive attention to combat the burden of CVD in women, because women have higher CVD mortality and morbidity rates than men do. As health literacy is paramount, the evaluation of awareness, and knowledge of CVD and its risk factors and their associations with the lifestyles of girls forms the basis for planning cardiovascular health promotion programs aiming to improve girls' immediate health and reduce the future burden of CVD among women. Methods A prospective cross-sectional study was conducted on a random sample of girls attending elementary and intermediate schools in Riyadh, Saudi Arabia. The girls completed a newly validated 24-item questionnaire that assessed their demographic data, lifestyles, and awareness and knowledge of CVD and its risk factors. Anthropometric and blood pressure measurements were obtained. Knowledge scores were calculated on the basis of correct responses and compared between subgroups via analysis of variance to determine associated factors. Results In total, 469 girls (mean age of 12.5 years) were included. Approximately 41.4% of them did not exercise or only exercised once a week. The dietary intake of important food groups was below or just at the minimal recommended servings for most. Overall, 44.1% were overweight/obese, and almost half were identified as hypertensive on the basis of a single resting measurement. Awareness of CVD as a dangerous disease in adults was 50.3%, whereas, cancer was identified by 61% of participants. Individual risk factors were identified by ≈ 25%, and 16.6% were not aware of any risk factors. The overall knowledge score of the participants was 2.6 (± 1.6) out of a total possible score of 8 representing 32.5% (± 20%). Knowledge levels were positively influenced by increasing school grade (P = 0.001) and family history of CVD (P < 0.001). There was no significant favorable association between improved knowledge level and lifestyle factors. Conclusion The awareness and knowledge of CVD among girls aged 8-16 years are poor and are largely dissociated from their lifestyle. Improved knowledge scores with increasing school grade and family history of CVD confirm a role for schools and families in improving girls' knowledge. Our findings mirror those obtained in older women, showing that misinformation among women starts in childhood and should be targeted early in life.